Legal Consequences of the Honorary Council's Decision on Ethical Violations by Constitutional Judges - Arifin, Anas -; Firmanto, Taufik (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2025)
This research aims: firstly to examine the position and authority of the Honorary Council, and secondly to examine the binding force and legal consequences of the Honorary Council's decisions. The method used is a normative legal research method with several approaches including: analytical approach, philosophical approach, statutory approach, conceptual approach and historical approach. The position of the Honorary Council is as a device established by the Constitutional Court to maintain and uphold the honor, nobility, dignity and Code of Ethics and Behavior of Constitutional Judges with authority, maintain the dignity and honor of the Constitutional Court, examine and decide on alleged violations of the Code of Ethics and Behavior of Constitutional Judges. can be done within a maximum period of 30 (thirty) working days from the time the report is recorded in e-BRLTP, and if the specified time is still in the process of being examined, it can be extended by another 15 (fifteen) working days. The decision of the Honorary Council has binding force for Constitutional Judges and the Constitutional Court. The legal consequences of the decision of the Honorary Council of the Constitutional Court are in the form of sanctions against judges who violate ethics, namely verbal warnings, written warnings, or dishonorable dismissal.